DIGITAL PLATFORMS AND MENTAL HEALTH: A CRITICAL REVIEW WITH A CASE STUDY ON NIGHT-TIME TELEPSYCHOLOGY (TILL NIGHT THERAPY) - Vitale, Francesca (International Journal of Engineering Technologies and Management Research, 2025)
The relentless evolution of digital technologies has ushered in an epochal shift in the paradigm of mental health, opening up unprecedented horizons for clinical practice, scientific investigation, and training in psychology. This contribution presents a critical, epistemologically grounded review of the scientific literature concerning digital platforms applied to psychology – rectius: eMental Health – with a particular focus on their applications, evidence of effectiveness, implementation challenges, and ethical and deontological implications. The various types of platforms are analyzed in extenso, including telepsychology, mobile mental health applications (mHealth), artificial intelligence (AI)-based interventions, and virtual reality (VR) and augmented reality (AR) applications, with an in-depth exegesis of the terminology and definitions in use. The analysis highlights the transformative potential of digital platforms in optimizing the accessibility, personalization, and effectiveness of psychological interventions; ex adverso, it highlights the need to address crucial issues related to quality, data security, regulation, and equity of access. The case of Till Night Therapy, an innovative Italian startup offering online psychological support and psychotherapy services during night-time hours, is presented, illustrating its strategic positioning and distinctive features. The epistemological and operational distinction between psychological support (counseling) and psychotherapy is also explored in depth, emphasizing the importance of a clear demarcation of their respective areas of intervention. It concludes with an examination of future research directions and implications for the training of mental health professionals, in the context of a hyper-digitalized society.